Literatur Review: Pasar Modal Syariah Terhadap Pertumbuhan Ekonomi Indonesia - Riswanda, Joni; Toriq, Agil; Attiyah, Dhiya Salfa; Tamara, Dita; Azkhari, Sisca (Jurnal Disrupsi Bisnis, 2024)
The purpose of this journal research is to conduct an analysis of the Islamic capital market on Indonesia's economic growth, this research uses the literature review study method with research data on articles and scientific journals as many as 5 journals that have been reviewed with a series of library data collection activities, reading and recording, and managing research materials. The results of the analysis show that Islamic stocks and sukuk have a positive and significant influence on national economic growth. This indicates that investment in both instruments can make an important positive contribution to Indonesia's economic development. Islamic stocks, showing a significant positive influence on economic growth, utilize sharia principles to provide sustainable profits for investors and a positive contribution to the national economy as a whole. Sukuk, as an instrument of Islamic debt, also plays an important role in supporting economic growth by providing a sustainable source of funding for economic projects. Although Islamic mutual funds have a significant negative influence on economic growth, these findings show that they still have the potential to support a sustainable Islamic financial sector in Indonesia.